LERO: um laboratório remoto de robótica educacional extensível e adaptável - FLORES, Críjina Chagas (2015)
Educational robotics is a tool that when used in academic environments encourage learning through playful activities. The major challenges related to the implementation of educational robotics environments are the costs to purchase equipment, the complexity of robotic infrastructure and the training of professionals involved in the process. One way to minimize these challenges is to provide access to remote laboratories of robotics. In this context, this work proposes the development of a Remote Laboratory of Educational Robotics (LERO). LERO aims to contribute to the teaching and learning of programming skills and robotics to different groups, stimulating the acquisition of knowledge. The LERO is a Web-based environment, extensible and adaptable and which includes an integrated development environment specialized in robot programming. The extensible term is used to characterize the ability of the system to incorporate new functionalities. The term adaptable term highlights that the environments can be used by a broad audience with varied level of knowledge and experience in terms of programming logic and robotics.